Improvement of Self Regulated Learning through Flex-Blended Learning Model Assisted by Learning Management System - Jihan Amami; Basori; Febri Liantoni (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2024)
Self-regulated learning is an essential aspect for students so that these students can organize and carry out learning activities independently. Self-regulated learning of students during the pandemic has a low average level. Self-regulated affects student achievement. The higher the level of student self-regulated learning, the better the achievement, and vice versa. This study aims to determine the differences and improvement of student self-regulated learning in applying the flex-type blended learning model assisted by Google Classroom. The method in this study uses quantitative methods with an experimental approach. Data collection was carried out through questionnaires and pretest-posttest as supporting data. The study's results showed differences in self-regulated learning before and after applying the flex-type blended learning model assisted by Google Classroom. This is evidenced by the results of the t-test on self-regulated learning, which shows significant differences. Then calculate the increase in self-regulated learning using N-Gain. In self-regulated learning, an N-Gain score of 0.323 is obtained, which means it is included in the medium category. Then to see the effect of self-regulated learning on student achievement, an N-Gain test was carried out on the pretest and post-test scores with a score of 0.436, which means it is included in the moderate category. From these results, it can be concluded that the increase in self-regulated learning is directly proportional to the rise in student achievement.